UZBEK APPLIED ART AND POTTERY: A CULTURAL JOURNEY OF CRAFTSMANSHIP, TECHNIQUES, AND SYMBOLISM - Baratbayev Batir Mamadjonovich (Galaxy International Interdisciplinary Research Journal, 2024)
This scientific article delves into the world of Uzbek applied art and pottery, exploring the rich cultural heritage, craftsmanship, techniques, and symbolic meanings embedded within these traditional art forms. Uzbekistan, situated at the crossroads of ancient trade routes, has a vibrant history of artistic expression, with applied art and pottery serving as significant cultural markers. The article investigates the historical context, materials, techniques, and aesthetic principles employed in Uzbek applied art and pottery. It examines the diverse range of forms and decorative motifs, highlighting their cultural significance and symbolic representations. Furthermore, the article addresses the role of applied art and pottery in Uzbek society, its preservation, and contemporary adaptations. By exploring Uzbek applied art and pottery, this article aims to celebrate the artistic traditions, promote cultural awareness, and inspire further research and appreciation of these remarkable art forms.